An institutional approach and input-output analysis for explaining the transformation of the Turkish economy - Emre Ünal (Journal of Economic Structures, 2018)
The increasing inconsistency in the Turkish economy gave rise to transformations necessitated by the manner of its growth and technological changes. Between 1923 and 1962, the Turkish economy was based on agricultural growth strategies, which spurred development in the manufacturing sector and caused technological change. Between 1962 and 1985, the Turkish economy developed under import substitution industrialization, with regulations based on domestic consumption growth strategies. In the early 1980s, most of the developed countries, in parallel with which Turkey had development policies, implemented strong institutional changes via deregulation policies, but Turkey could not produce the necessary configurations in accord with open and export growth economies. The period between 1985 and 2003 was a long transformational period for Turkey vying to be a stable export growth country. This slow transformation was caused by path dependency and had been based on regulations that destabilized Turkey and deepened problems remaining from previous periods. Post-2003, the Turkish economy was able to develop more consistent export growth by forced institutional changes, but its macroeconomic factors still do not show institutional complementarity.
Keywords: C6; E6; F4; O4; 330; Agricultural growth; Domestic consumption growth; Export growth; Institutional factors; Stylized facts of structural transformation; Input-output analysis